Controlling livestock diseases in the tropics by breeding: A perspective - Kasali, O.B.; Njau, B.C.; Bekele, T. (Kluwer Academic Publishers, 1988)
Reviews the control of livestock diseases in the tropics by breeding, with particular reference to trypanosomiasis, and gastrointestinal parasites. Looks at the N'Dama breeding programme.